A Review on Mycotoxins and Microfungi in Spices in the Light of the Last Five Years - Pickova, Darina; Ostry, Vladimir; Malir, Jan; Toman, Jakub; Malir, Frantisek (Toxins, 2020)
Spices are imported worldwide mainly from developing countries with tropical and/or subtropical climate. Local conditions, such as high temperature, heavy rainfall, and humidity, promote fungal growth leading to increased occurrence of mycotoxins in spices. Moreover, the lack of good agricultural practice (GAP), good manufacturing practice (GMP), and good hygienic practice (GHP) in developing countries are of great concern. This review summarizes recent data from a total of 56 original papers dealing with mycotoxins and microfungi in various spices in the last five years. A total of 38 kinds of spices, 17 mycotoxins, and 14 microfungi are discussed in the review. Worldwide, spices are rather overlooked in terms of mycotoxin regulations, which usually only cover aflatoxins (AFs) and ochratoxin A (OTA). In this paper, an extensive attention is devoted to the limits on mycotoxins in spices in the context of the European Union (EU) as well as other countries. As proven in this review, the incidence of AFs and OTA, as well as other mycotoxins, is relatively high in many spices; thus, the preparation of new regulation limits is advisable.
Keywords: Food Contamination; spices; Spices; Time Factors; Animals; mycotoxin; Mycotoxins; kontaminace potravin; Aflatoxins; časové faktory; Humans; Internationality; internacionalita; Fungi; koření; microfungi; aflatoxiny; contamination; zvířata; mykotoxiny; houby; lidé